TEACHING LISTENING AND ITS PECULIARITIES IN FOREIGN LANGUAGE LEARNING - Ataxojayev Toxirjon Maxmudjonovich (Galaxy International Interdisciplinary Research Journal, 2024)
This article deals with the study of the peculiarities of teaching listening in teaching FL, the difficulties students face and the ways of overcoming these difficulties have been investigated in detail.